2022
DOI: 10.21037/jtd-21-1624
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical segmentectomy under uniportal video-assisted thoracoscopic surgery for early staged non-small cell lung cancer: a case report

Abstract: Background: Anatomical segmentectomy has become more and more universal in thoracic surgery because of the increasing detection of pulmonary nodules with ground-glass opacity (GGO), most of which proved early staged non-small cell lung cancer (NSCLC) postoperative. With the advantage of preservation of normal lung tissues, segmentectomy may be performed by surgeons when computed tomography (CT) scan shows pure GGO or multiple GGOs appearing. Especially when the patients with poor cardiopulmonary function or se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…As reported in the international multidisciplinary team discussion titled "Anatomical segmentectomy under uniportal video-assisted thoracoscopic surgery (VATS) for early staged non-small cell lung cancer: a case report" by Wang et al (1), anatomical segmentectomy under uniportal VATS can be a feasible and safe minimally invasive procedure. The authors also concluded that uniportal segmentectomy has equivalent oncological outcomes to lobectomy for early-stage lung cancer but needs to be performed at an experienced medical center.…”
mentioning
confidence: 99%
“…As reported in the international multidisciplinary team discussion titled "Anatomical segmentectomy under uniportal video-assisted thoracoscopic surgery (VATS) for early staged non-small cell lung cancer: a case report" by Wang et al (1), anatomical segmentectomy under uniportal VATS can be a feasible and safe minimally invasive procedure. The authors also concluded that uniportal segmentectomy has equivalent oncological outcomes to lobectomy for early-stage lung cancer but needs to be performed at an experienced medical center.…”
mentioning
confidence: 99%
“…The article "Anatomical segmentectomy under uniportal video-assisted thoracoscopic surgery for early staged non-small cell lung cancer" clearly describes the issues mentioned above (9). The article consists of two parts, the first section shows how a surgeon can perform an uniportal segmentectomy, and the second section deals with the main issues in uniportal lung cancer surgery through interactive discussion.…”
mentioning
confidence: 99%
“…In the case report by Wang et al (12), the uniportal videoassisted thoracoscopic segmentectomy was shown as a right apical (S1) segmentectomy and was relatively complex. This procedure is currently the most popular among minimally invasive surgeries, and the case report contained useful information that included the details of procedural steps, the understanding of the precise anatomies of pulmonary vasculatures and bronchi using a three-dimensional (3D) reconstruction, and the characteristics of uniportal videoassisted thoracoscopic surgery (VATS).…”
mentioning
confidence: 99%
“…In addition, the patient described in the report by Wang et al (12) had other lung nodules at the same time and therefore needed a surgical strategy of resection planning for multiple nodules. We occasionally encounter cases with multiple small-sized GGO-dominant tumors, such as that of this patient.…”
mentioning
confidence: 99%
See 1 more Smart Citation